2002
DOI: 10.1021/ja012545e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Electrochemical Analysis of Dissociative Electron Transfers Proceeding through Formation of Loose Radical Anion Species:  Reduction of Symmetrical and Unsymmetrical Disulfides

Abstract: The dissociative reduction of a series of symmetrical (RSSR, R = H, Me, t-Bu, Ph) and unsymmetrical disulfides (RSSR', R = H, R' = Me and R = Ph, R' = Me, t-Bu) was studied theoretically, by MO ab initio calculations and, for five of them, also experimentally, by convolution voltammetry in N,N-dimethylformamide. The reduction is dissociative but proceeds by a stepwise mechanism entailing the formation of the radical anion species. The electrochemical data led to estimated large intrinsic barriers, in agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
100
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 88 publications
13
100
1
Order By: Relevance
“…Equilibrium constants for this association reaction are in the range 10 2 -10 4 M -1 (Mezyk and Armstrong, 1999). Direct evidence for the reaction of the thiyl radical and thiolate to the disulfide radical anion was recognized by EPR in the enzymatic process, at least for the E441Q R1 mutant (Lawrence et al, 1999 Figure 13 Step (4) as suggested by Cerqueira et al (2004b) and by Pelmenschikov et al (2004). of disulfides are in the range of -1.9 to -2.3 V SCE for dialkyl derivatives (Mezyk and Armstrong, 1999;Antonello et al, 2002); hence, disulfide radical anions are strong reducing agents that can reduce carbonyl derivatives, in particular if these are involved in hydrogen bonding (Oelgemö ller et al, 2002).…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 99%
“…Equilibrium constants for this association reaction are in the range 10 2 -10 4 M -1 (Mezyk and Armstrong, 1999). Direct evidence for the reaction of the thiyl radical and thiolate to the disulfide radical anion was recognized by EPR in the enzymatic process, at least for the E441Q R1 mutant (Lawrence et al, 1999 Figure 13 Step (4) as suggested by Cerqueira et al (2004b) and by Pelmenschikov et al (2004). of disulfides are in the range of -1.9 to -2.3 V SCE for dialkyl derivatives (Mezyk and Armstrong, 1999;Antonello et al, 2002); hence, disulfide radical anions are strong reducing agents that can reduce carbonyl derivatives, in particular if these are involved in hydrogen bonding (Oelgemö ller et al, 2002).…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 99%
“…[20] On top of this, our knowledge on the mechanistic details of the SÀS bond fission has been limited by the fact that most of these attempts were based on symmetric model systems, in which the two substituents attached to the SÀS bridge were identical. Actually, to the best of our knowledge, only Antonello et al [21] have addressed the ECD in RSSR' unsymmetrical disulfides, where the R and R' substituents were alkyl or phenyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the electrochemical behavior of DDS and C 6 H 5 SH on GC electrode allows to clarify the nature of the ET process in aprotic solvent (ACN), and the overall electrochemical reduction mechanism. The S À S bond free energy was calculated using E8 values obtained by a convolution method [21,22,23].…”
Section: Introductionmentioning
confidence: 99%